Pantun translations into English in women’s writings in twentieth century British Malaya - Shanmugam, Krishnavanie (Journal of Modern Languages, 2017)
This paper is part of a larger historical study on Malay pantun translations into English since the nineteenth century. Two of the main aims of the historical study were: (1) to describe the prevalent translation styles adopted by the translators of pantun from the nineteenth century to the present times and (ii) to identify the extent to which the translation style is influenced by the skopos or translation purpose. The discussion in this paper is similarly directed by these two aims and is especially devoted to the only two women writers in British Malaya that is, Katherine Sim and Martha Blanche Lewis who highlighted the importance of the Malay pantun as an essential element of the Malay language and the ingenuity of the Malay mind. Sim’s and Lewis’s reference to/discussion of the pantun via translations in English in their referential texts (which total to about less than 160 pantun translations) contributed significantly towards promoting the pantun to an English readership in their times. The categorization of translation styles in this study is based on Christiane Nordâ€Ÿs functional typology (1997), which is namely divided into two large categories: documentary (grammatically literal) translations and instrumental (creatively modulated/literary) translations